Derivation and evaluation of Landsat-derived annual aboveground biomass maps for Arctic and Boreal North America, 1984-2022 - Wanwan Liang; Olivier van Lier; Mark A. Friedl; James T. Randerson; Brendan M. Rogers; Arden Burrell; Kai-Ting Hu; Piotr Tompalski; Matthew J. Macander; Daryl Yang; Douglas C. Morton; Eric Bullock; et al. (Remote Sensing of Environment, 2026)

Burned area mapping across the Arctic-boreal zone with Landsat and Sentinel-2 imagery - Stefano Potter; Yili Yang; Arden Burrell; Anna Talucci; Andrew A. Clelland; Sander Veraverbeke; James T. Randerson; Scott J. Goetz; Logan T. Berner; Michelle C. Mack; Xanthe J. Walker; Susan M. Natali; et al. (International Journal of Remote Sensing, 2026)

Ionophore susceptibility of Eimeria zaria: First characterisation in a cryptic Eimeria species of chickens - Marta Raffaelli; José Manuel Jaramillo-Ortiz; Marili Vasilogianni; Melanie C. Hay; Daniel Ngugi; Caela Burrell; Virginia Marugan-Hernandez; Stefania Perrucci; Dong Xia; Damer P. Blake (Veterinary Parasitology, 2026)

Ice regimes, ice jams, and a changing hydroclimate, Saint John (Wolastoq) River, New Brunswick, Canada - Brent Newton; Spyros Beltaos; Brian C. Burrell (Natural Hazards, 2024)
Ice formation, growth, and breakup along the Saint John River (SJR) affects its hydraulic and ecological regimes and leads to the potential for ice jamming that has caused severe flooding and ice runs resulting in loss of life, property damage, and loss of, or damage to, infrastructure. A synopsis of ice regimes and ice jamming along the SJR from Dickey, Maine, USA to Woodstock, New Brunswick, Canada is summarized in this paper. Trends in relevant hydroclimatic variables such as monthly mean air temperature (December to April), total winter snow (December to March), length of the ice season, rainfall, and monthly mean and peak winter and spring flows are discussed. Projections of future ice regimes under a changing climate are provided, with anticipated changes in the ice regime of the SJR explained in the wider context of changes to the cryosphere.

Potential Application of Orofacial MSCs in Tissue Engineering Nerve Guidance for Peripheral Nerve Injury Repair - Qingyu Meng; Justin C. Burrell; Qunzhou Zhang; Anh D. Le (Stem Cell Reviews and Reports, 2023)

The effect of arterial cannula tip position on differential hypoxemia during venoarterial extracorporeal membrane oxygenation - Avishka Wickramarachchi; Aidan J. C. Burrell; Andrew F. Stephens; Michael Šeman; Ashkan Vatani; Mehrdad Khamooshi; Jaishankar Raman; Rinaldo Bellomo; Shaun D. Gregory (Physical and Engineering Sciences in Medicine, 2023)

Neural Crest Stem-Like Cells Non-genetically Induced from Human Gingiva-Derived Mesenchymal Stem Cells Promote Facial Nerve Regeneration in Rats - Qunzhou Zhang; Phuong D. Nguyen; Shihong Shi; Justin C. Burrell; Qilin Xu; Kacy D. Cullen; Anh D. Le (Molecular Neurobiology, 2018)

Nuclear organization of the African elephant (Loxodonta africana) amygdaloid complex: an unusual mammalian amygdala - Aude’Marie Limacher-Burrell; Adhil Bhagwandin; Busisiwe C. Maseko; Paul R. Manger (Brain Structure and Function, 2017)

Nuclear organization of the rock hyrax (Procavia capensis) amygdaloid complex - Aude-Marie Limacher-Burrell; Adhil Bhagwandin; Nadine Gravett; Busisiwe C. Maseko; Paul R. Manger (Brain Structure and Function, 2016)

Fluorescence in situ hybridization analysis of hindgut bacteria associated with the development of equine laminitis - Gabriel J. Milinovich; Darren J. Trott; Paul C. Burrell; Emma L. Croser; Rafat A. M. Al Jassim; John M. Morton; Andrew W. van Eps; Christopher C. Pollitt (Environmental Microbiology, 2008)

Phylogenetic analysis of Porphyromonas species isolated from the oral cavity of Australian marsupials - Deirdre Mikkelsen; Gabriel J. Milinovich; Paul C. Burrell; Sharnan C. Huynh; Lyndall M. Pettett; Linda L. Blackall; Darren J. Trott; Philip S. Bird (Environmental Microbiology, 2008)
Summary Porphyromonas species are frequently isolated from the oral cavity and are associated with periodontal disease in both animals and humans. Black, pigmented Porphyromonas spp. isolated from the gingival margins of selected wild and captive Australian marsupials with varying degrees of periodontal disease (brushtail possums, koalas and macropods) were compared phylogenetically to Porphyromonas strains from non‐marsupials (bear, wolf, coyote, cats and dogs) and Porphyromonas gingivalis strains from humans using 16S rRNA gene sequence analysis. The results of the phylogenetic analysis identified three distinct groups of strains. A monophyletic P. gingivalis group (Group 1) contained only strains isolated from humans and a Porphyromonas gulae group (Group 2) was divided into three distinct subclades, each containing both marsupial and non‐marsupial strains. Group 3, which contained only marsupial strains, including all six strains isolated from captive koalas, was genetically distinct from P. gulae and may constitute a new Porphyromonas species.

Fluorescence in situ hybridization analysis of hindgut bacteria associated with the development of equine laminitis - Gabriel J. Milinovich; Darren J. Trott; Paul C. Burrell; Emma L. Croser; Rafat A. M. Al Jassim; John M. Morton; Andrew W. Van Eps; Christopher C. Pollitt (Environmental Microbiology, 2007)
Summary Carbohydrate‐induced laminitis in horses is characterized by marked changes in the composition of the hindgut microbiota, from a predominantly Gram‐negative population to one dominated by Gram‐positive bacteria. The objective of this study was to monitor changes in the relative abundance of selected hindgut bacteria that have previously been implicated in the pathophysiology of equine laminitis using fluorescence in situ hybridization (FISH). Caecal cannulae were surgically implanted in five Standardbred horses and laminitis induced by oral administration of a bolus dose of oligofructose. Caecal fluid and faecal specimens were collected over a 48 h period at 2 to 4 h intervals post‐oligofructose administration and subjected to FISH using probes specific for nine bacterial groups to determine changes in their relative abundance compared with total bacteria hybridizing to the generic EUBMIX probe. Additionally, hoof biopsies were taken over the course of the experiment at 6 h intervals and evaluated for histopathological changes consistent with laminitis, allowing changes in hindgut microbiota to be correlated with the onset of lesions in the foot. Of the microorganisms specifically targeted, streptococci of the Streptococcus bovis / equinus complex were the only bacteria that consistently proliferated in both caecal fluid and faeces immediately before the onset of histological signs of laminitis. Furthermore, lactobacilli, Enterobacteriaceae , Allisonella histaminiformans , enterococci, Bacteroides fragilis , Mitsuokella jalaludinii and Clostridium difficile did not establish significant populations in the hindgut before the onset of equine laminitis.

Changes in equine hindgut bacterial populations during oligofructose‐induced laminitis - G. J. Milinovich; D. J. Trott; P. C. Burrell; A. W. Van Eps; M. B. Thoefner; L. L. Blackall; R. A. M. Al Jassim; J. M. Morton; C. C. Pollitt (Environmental Microbiology, 2006)
Summary In the horse, carbohydrate overload is thought to play an integral role in the onset of laminitis by drastically altering the profile of bacterial populations in the hindgut. The objectives of this study were to develop and validate microbial ecology methods to monitor changes in bacterial populations throughout the course of experimentally induced laminitis and to identify the predominant oligofructose‐utilizing organisms. Laminitis was induced in five horses by administration of oligofructose. Faecal specimens were collected at 8 h intervals from 72 h before to 72 h after the administration of oligofructose. Hindgut microbiota able to utilize oligofructose were enumerated throughout the course of the experiment using habitat‐simulating medium. Isolates were collected and representatives identified by 16S rRNA gene sequencing. The majority of these isolates collected belonged to the genus Streptococcus , 91% of which were identified as being most closely related to Streptococcus infantarius ssp. coli . Furthermore, S . infantarius ssp. coli was the predominant oligofructose‐utilizing organism isolated before the onset of lameness. Fluorescence in situ hybridization probes developed to specifically target the isolated Streptococcus spp. demonstrated marked population increases between 8 and 16 h post oligofructose administration. This was followed by a rapid population decline which corresponded with a sharp decline in faecal pH and subsequently lameness at 24–32 h post oligofructose administration. This research suggests that streptococci within the Streptococcus bovis / equinus complex may be involved in the series of events which precede the onset of laminitis in the horse.

Erratum for “Fluctuating Asymmetry and Growth as Biomarkers for Exposure to Androgen Disrupting Chemicals in Japanese Quail” [10.1007/s10646-005-0013-9(10646-2005-13 Quinn)] - Michael J. Quinn; C. L. Summitt; K. Burrell; M. A. Ottinger (Ecotoxicology, 2005)

Effect of deletion and the site of insertion in double copy anti-tat retroviral vectors: viral titres and production of anti-tat mRNA - J. M. Carr; J. K. Calvert; R. Kumar; C. J. Burrell; P. Li (Archives of Virology, 2001)

HIV DNA integration during cell-to-cell transmission of infection: evidence for partially integrated DNA structures in acutely infected cells - T. Kok; P. Li; C. J. Burrell (Archives of Virology, 2001)

Further characterization of HIV RNA synthesis early after cell-to-cell transmission infection - T-W. Kok; P. Li; C. J. Burrell (Archives of Virology, 1998)

AZT blocks down-regulation of IL-2 and IFN-γ gene expression in HIV acutely infected cells - J. Fan; P. Li; T.-W. Kok; C. J. Burrell (Archives of Virology, 1997)

Establishment of persistent HIV-1 infection in vitro is accompanied by reduction of NF-?B activity - X. Zhang; P. Li; C. J. Burrell (Archives of Virology, 1994)

Isolation of reovirus type 2 from respiratory tract of sheep - D. R. Snodgrass; C. Burrells; P. W. Wells (Archives of Virology, 1976)

Immunoglobulins, antibodies and inhibitors of Parainfluenza 3 virus in respiratory secretions of sheep - W. D. Smith; P. W. Wells; C. Burrells; A. McL Dawson (Archives of Virology, 1975)